RETRACTED: Perbedaan Kreativitas Anak Kelompok A Antara Kegiatan Kolase Bahan Alam dan Kolase Bahan Kertas - Sri Widayati; Nurhenti Simatupang; Kartika Rinakit Adhe; Nurul Ulfatul Hasanah (Universitas Ahmad Dahlan, 2019)
Following a rigorous, carefully concerns and considered review of the article published in JECCE (Journal of Early Childhood Education and Care) to article entitled :Â Perbedaan Kreativitas Anak Kelompok A Antara Kegiatan Kolase Bahan Alam dan Kolase Bahan Kertas Vol 2, No 1, pp. 21-29, March 2019,This paper has been found to be in violation of the JECCE Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Jurnal Teratai, Vol. 7, No. 3, pp. 1-6 , 2018.The document and its content has been removed from JECCEi, and reasonable effort should be made to remove all references to this article.